COVID-19 and its Impact on Labour Migration: The Case of Asia - Karaleka, Antonia Nefeli (HAPSc Policy Briefs Series, 2021)
Globalized economy relies on labour migration. In the current effort to rebuild the future in an early post-COVID world, the impact of this health crisis had on the international migration workers should be studied. For more than a year now, professionals of different skill levels have been obliged to either return to their home country or to stay trapped in their destination country unemployed or with little access to social security or the ability for self-protection by potential virus infection. The impact was huge both for the origin and the destination countries. One of the most important effects was on international remittances. Some initiatives were taken to manage this situation. This policy brief aims to enlighten new areas on which extra effort should be made regarding labour migration.